The behaviour of populist parties in parliament. The policy agendas of populist and other political parties in the Italian question time. (22nd November 2022) - Cavalieri, Alice; Froio, Caterina
Abstract: This article addresses the question of whether populist parties behave differently from other political parties in parliament. Building on the attention-based perspective of the study of policy agendas, we map issue emphasis in parliamentary questions in Italy over more than two decades (1996–2019). The paper is innovative as it compares populist and non-populist parties in government and in opposition. Using data from the Italian Policy Agendas Project and The PopuList, we find mixed evidence. Specifically, we show that populist parties behave differently from other parties only when they are in opposition (signalling that they are different from 'elite' ones) but not when in government (signalling that they are 'competent' policymakers). While the results are exploratory and drawn from the Italian context, this study contributes to deflate the myth of populists' exceptionalism, at least in terms of their behaviour in parliament. As such, it holds broader implications for the scholarly understanding of party government and the so-called 'normalization' of populism in contemporary democracies.